Ethnomathematical exploration in the designs and restoration processes of the heritage churches of Chiloe-Chile (2023)
The objective of this research was to explore the mathematical notions present in the daily practice of restoration of the heritage churches of Chiloé, Chile. Under a qualitative-ethnographic methodological path, a semi-structured interview protocol was implemented, applied to five carpenters who worked in church restoration through the Friends of the Churches of Chiloé Foundation. The results show that daily practice involves five moments of restoration: installation of tasks, disarmament stage, foundations, restructuring and completions. They include mathematical notions associated with measurement systems, geometric figures (representations of the parallelepiped, pyramid and cube) and their properties, reference systems, numbers, functions and their applications, angles, straight lines, among others. These findings are an input for the development of contextualized tasks that promote mathematical knowledge in students and encourage the appreciation of their own culture, connecting it with the institutional mathematics developed in the classrooms by teachers and students.